2015
DOI: 10.1016/j.actbio.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol) diacrylate/hyaluronic acid semi-interpenetrating network compositions for 3-D cell spreading and migration

Abstract: To serve as artificial matrices for therapeutic cell transplantation, synthetic hydrogels must incorporate mechanisms enabling localized, cell-mediated degradation that allows cell spreading and migration. Previously, we have shown that hybrid semi-interpenetrating polymer networks (semi-IPNs) composed of hydrolytically degradable PEG-diacrylates (PEGdA), acrylate-PEG-GRGDS, and native hyaluronic acid (HA) support increased cell spreading relative to fully synthetic networks that is dependent on cellular hyalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…As a potential improvement, we have recently shown that PEG-bis-AP can be combined with two other PEG-diacrylate derivatives possessing faster and slower degradation rates to produce semi-IPNs with more finely controlled degradation over 5 weeks. 38 A second potential limitation is that cell spreading within the networks via HA degradation accelerates between about 4–12 days post-encapsulation, leading to a rapid rise in DX release. In this study, we conjugated DX to HA at a relatively low degree of substitution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a potential improvement, we have recently shown that PEG-bis-AP can be combined with two other PEG-diacrylate derivatives possessing faster and slower degradation rates to produce semi-IPNs with more finely controlled degradation over 5 weeks. 38 A second potential limitation is that cell spreading within the networks via HA degradation accelerates between about 4–12 days post-encapsulation, leading to a rapid rise in DX release. In this study, we conjugated DX to HA at a relatively low degree of substitution.…”
Section: Resultsmentioning
confidence: 99%
“…3538 We hypothesized that dexamethasone covalently conjugated to HA through a double ester linkage (HA-DXM) and PEG-bis-AP could form semi- IPN structures that release free dexamethasone in response to cell-mediated remodeling and stimulate osteogenic differentiation of encapsulated MSCs (Figure 1). In this study, we synthesized HA-DXM and characterized DX release in response to chemical and enzymatic hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts cultured for 7 d in the thin gelatin hydrogels under static conditions also exhibited similar elongation (Figure S5, Supporting Information). Anchorage‐dependent fibroblasts can only survive when attached to ECM and a stretched cell morphology is both an indication of health and necessary for migration, proliferation, and differentiation . It is known that gelatin, the denatured form of collagen, retains MMP‐sensitive degradation sites .…”
mentioning
confidence: 99%
“…simply curried under UV lamp). Furthermore, it is good choice to be used in biomedical application due to its bio-compatibility [23,24]. This novel polymer fiber-optic sensor exhibits a sensitivity of up to −0.41 nm/pH and an average response time of 30 s. As the sensor was developed toward bio-medical application, only acidic range was considered [24].…”
Section: Introductionmentioning
confidence: 99%